2006
DOI: 10.2152/jmi.53.140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of saliva collection method on the concentration of protein components in saliva

Abstract: In order to clarify how we collect saliva for analyzing salivary protein in aged subjects who can not eat well, we compared the effects of suction, spitting and the swab saliva collection method on the yield of protein components in saliva samples from normal volunteers. The saliva collected by suction, spitting and the swab method were designated as, Saliva I, II and III, respectively. The saliva volume collected by Saliva I was about 2-fold greater than that by of Saliva II and III. This is mainly due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Furthermore, saliva and analyte recovery may vary considerably in each method, mainly owing to the fact that some analytes may adhere to the cotton, causing false lower values (14,22,37) .…”
Section: Methods For Saliva Collectionmentioning
confidence: 99%
“…Furthermore, saliva and analyte recovery may vary considerably in each method, mainly owing to the fact that some analytes may adhere to the cotton, causing false lower values (14,22,37) .…”
Section: Methods For Saliva Collectionmentioning
confidence: 99%
“…Resting salivary flow was measured by the spitting method [22,23], which involved collecting saliva spit into paper cups over a 15-min period and measuring the content. A result of <1.5 mL/15 min was considered as low resting salivary flow.…”
Section: Salivary Secretion Measurementmentioning
confidence: 99%
“…Unstimulated, slightly stimulated, and stimulated saliva is collected using the spitting, aspiration, and swab methods, respectively. Michishige et al demonstrated that, among the 3 saliva collection methods, the spitting and aspiration methods showed a significant positive correlation of salivary IgA concentrations [32]. The association between salivary IgA and URTI risk has been exhibited not only through salivary IgA concentrations but also through salivary IgA secretion rate [16,17,18,19,20,21,22,23,24].…”
mentioning
confidence: 99%
“…Correlation was analyzed using Pearson’s correlation coefficient.). Michishige et al reported that the salivary IgA concentration was significantly correlated in samples collected by the aspiration and spitting methods [32]. Correlation between the salivary secretion rate in samples collected by aspiration and spitting methods is expected, since unstimulated and slightly stimulated saliva are collected using these methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation